The Final Days - Woodward, Bob adn Bernstein, Carl (New York Simon and Schuster, 1976)
The Washington Post reporters draw on interviews, leaks, and investigations to reconstruct the events and circumstances, in and outside the White House, during the unsettled and unsettling final weeks of the Nixon administration.
Include Illustration and Index
Keywords: Nixon, Richard M. (Richard Milhous), 1913-1994 -- Impeachments -- Resignation from office